+0  
 
0
236
6
avatar+80 

can I multiply (2x+5y)(3x^2-4xy+2y^2)?

gadzooks1753  Nov 16, 2017
 #1
avatar
-1

Expand the following:
(2 x + 5 y) (3 x^2 - 4 x y + 2 y^2)

(3 x^2 - 4 x y + 2 y^2) (2 x + 5 y) = 2 x (3 x^2 - 4 x y + 2 y^2) + 5 y (3 x^2 - 4 x y + 2 y^2):
2 x (3 x^2 - 4 x y + 2 y^2) + 5 y (3 x^2 - 4 x y + 2 y^2)

2 x (3 x^2 - 4 x y + 2 y^2) = 2 x×3 x^2 + 2 x (-4 x y) + 2 x×2 y^2:
2×3 x x^2 - 4×2 x x y + 2×2 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

2 x×3 x^2 = 2 x^(1 + 2)×3:
2×3 x^(1 + 2) - 4×2 x x y + 2×2 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

1 + 2 = 3:
2×3 x^3 - 4×2 x x y + 2×2 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

2×3 = 6:
6 x^3 - 4×2 x x y + 2×2 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

2 x (-4) x y = 2 x^2 (-4) y:
6 x^3 + -4×2 x^2 y + 2×2 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

2 (-4) = -8:
6 x^3 + -8 x^2 y + 2×2 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

2×2 = 4:
6 x^3 - 8 x^2 y + 4 x y^2 + 5 y (3 x^2 - 4 x y + 2 y^2)

5 y (3 x^2 - 4 x y + 2 y^2) = 5 y×3 x^2 + 5 y (-4 x y) + 5 y×2 y^2:
6 x^3 - 8 x^2 y + 4 x y^2 + 5×3 y x^2 - 4×5 y x y + 5×2 y y^2

5×3 = 15:
6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 - 4×5 y x y + 5×2 y y^2

5 y (-4) x y = 5 y^2 (-4) x:
6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 + -4×5 y^2 x + 5×2 y y^2

5 (-4) = -20:
6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 + -20 y^2 x + 5×2 y y^2

5 y×2 y^2 = 5 y^(1 + 2)×2:
6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 - 20 y^2 x + 5×2 y^(1 + 2)

1 + 2 = 3:
6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 - 20 y^2 x + 5×2 y^3

5×2 = 10:
6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 - 20 y^2 x + 10 y^3

Grouping like terms, 6 x^3 - 8 x^2 y + 4 x y^2 + 15 y x^2 - 20 y^2 x + 10 y^3 = 10 y^3 + (4 x y^2 - 20 x y^2) + (15 x^2 y - 8 x^2 y) + 6 x^3:
10 y^3 + (4 x y^2 - 20 x y^2) + (15 x^2 y - 8 x^2 y) + 6 x^3

4 (x y^2) - 20 (x y^2) = -16 (x y^2):
10 y^3 + -16 x y^2 + (15 x^2 y - 8 x^2 y) + 6 x^3

15 (x^2 y) - 8 (x^2 y) = 7 (x^2 y):
10y^3 - 16xy^2 + 7x^2y + 6x^3

Guest Nov 16, 2017
 #2
avatar+80 
-1

so i can multiply this

gadzooks1753  Nov 16, 2017
 #3
avatar+771 
-1

Yes.

AdamTaurus  Nov 16, 2017
 #4
avatar+80 
-1

is the answer 6x^3+7x^2y-16xy^2+10y^3

gadzooks1753  Nov 16, 2017
 #5
avatar+80 
-1

nevermind on that answer

gadzooks1753  Nov 16, 2017
 #6
avatar+771 
0

(2x+5y)(3x^2-4xy+2y^2)

First, multiply the first term in the first parenthesis by every term in the polynomial.

\((2x)(3x^2)+(2x)(-4xy)+(2x)(2y^2)+(5y)(3x^2-4xy+2y^2)\)

Simplify.

\((2x)(3x^2)=6x^3, (2x)(-4xy)=-8x^2y, (2x)(2y^2)=4xy^2\)

\(6x^3-8x^2y+4xy^2+(5y)(3x^2-4xy+2y^2)\)

Now distribute the 5y.

\(6x^3-8x^2y+4xy^2+(5y)(3x^2)+(5y)(-4xy)+(5y)(2y^2)\)

Simplify.

\((5y)(3x^2)=15x^2y, (5y)(-4xy)=-20xy^2, (5y)(2y^2)=10y^3\)

\(6x^3-8x^2y+4xy^2+15x^2y-20xy^2+10y^3\)

Reorganize.

\(6x^3-8x^2y+15x^2y+4xy^2-20xy^2+10y^3\)

Combine like terms.

\(-8x^2y+15x^2y=7x^2y, 4xy^2-20xy^2=-16xy^2\)

\(6x^3+7x^2y-16xy^2+10y^3\)

This is the same as Guest's answer but LaTeX makes it easier to read.

AdamTaurus  Nov 16, 2017

11 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.